Predictive Value of Hypoalbuminemia for Contrast-Associated Acute Kidney Injury: A Systematic Review and Meta-Analysis. (August 2021) - Liu, Liwei; Lun, Zhubin; Wang, Bo; Lei, Li; Sun, Guoli; Liu, Jin; Guo, Zhaodong; He, Yibo; Song, Feier; Liu, Bowen; Chen, Guanzhong; Chen, Shiqun; et al.
Contrast-associated acute kidney injury (CA-AKI) is a major adverse complication of intravascular administration of contrast medium. Current studies have shown that hypoalbuminemia might be a novel risk factor of CA-AKI. This systematic review and meta-analysis was performed to evaluate the predictive value of hypoalbuminemia for CA-AKI. Relevant studies were identified in Ovid-Medline, PubMed, Embase, and Cochrane Library up to December 31, 2019. Two authors independently screened studies, consulting with a third author when necessary to resolve discrepancies. The pooled odds ratio (OR) was calculated to assess the association between hypoalbuminemia and CA-AKI using a random-effects model or fixed-effects model. Eight relevant studies involving a total of 18 687 patients met our inclusion criteria. The presence of hypoalbuminemia was associated with an increased risk of CA-AKI development (pooled OR: 2.59, 95% CI: 1.80-3.73). Hypoalbuminemia is independently associated with the occurrence of CA-AKI and may be a potentially modifiable factor for clinical intervention. This systematic review and meta-analysis was registered in PROSPERO (CRD42020168104).